Roald Amundsens's Tent at the South Pole - Barr, Susan (Antarctic Resolution, 2021)
Keywords: Antarktis; Norge; Roald Amundsen; Sydpolsekspedisjonen; historie

Norway's path to the Antarctic Treaty - Jølle, Harald Dag (Fram forum, 2021)
Keywords: Antarktis; Antarktistraktaten 1959; Norge; ekspedisjoner; historie; hvalfangst; internasjonal; jus; politikk

Den siste olje - Berge, Aslak (Octavian forlag AS, 2019)
Over seks tiår fylte glinsende fett fra hundretusenvis av hval råstoffbehov til multinasjonale konserners margarin- og såpeprodukter. Hoffleverandørene var norske hvalfangere. Fra spekkjelene like etter århundreskiftet ble fyrt opp på Sør-Georgia til det flytende kokeriet Kosmos IV ankret opp i Sandefjord på slutten av 1960-tallet, skulle hvalfangst dominere og forme utviklingen av finansmarked, konsumvarer og kapitalisme i Norge. Dette er en fortelling om eksplosivt voksende rikdom og merkevarebygging, men også en biologisk tragedie. Et nådeløst møte mellom jordens største dyr, effektiv fangsteknologi og konsumindustri. Dette er en flerfasettert historie om et kapitalfattig lands industrialisering, skattesky redere og multinasjonale fettkjemper, men også om ubegrensede offer og tap. Om norsk polarimperialisme og globalt salg utfordret av stormakter og skiftende konjunkturer. Dette er historien om "Den siste olje".
Keywords: Norge; Sørishavet; historie; hvalfangstindustri; hvalindustri; pelagisk; økonomi

Hvaleventyret : hvordan vi nesten utryddet det største dyret som har levd - Tjernshaugen, Andreas (Kagge, 2018)
Historien om jakten på blåhvalen, verdens største dyr. Blåhvalen var nær ved å bli utryddet av den moderne hvalfangsten med raske båter, sprenggranater og harpunkanon. Lenge utgjorde Vestfold verdens hvalfangstsentrum, og på det meste forlot ti tusen norske menn familien og dro på hvalfangst i fremmede farvann. Det var et blodslit, og et eventyr. Helt fra starten kom det advarsler om at hvalene kunne bli utryddet. For blåhvalen var det på nære nippet. Underarten i Antarktis, som blir aller størst, regnes fortsatt som kritisk truet. I sluttspillet om blåhvalens skjebne ble Norge utfordret av både Storbritannia og Nazi-Tyskland, Japan og Sovjetunionen, som kastet seg inn i kampen om Sørishavets rikdommer. "Hvaleventyret" er en medrivende historie om blåhvalen og hvalfangsten. Den forteller om hvalenes årlige trekk mellom isen og varmere hav, om hvalfangernes livsfarlige pionerferder i polhavene, og om kampen for å redde de siste blåhvalene.
Keywords: Nordmenn; Norge; Sørishavet; dyrevern; hvaler; hvalfangst; hvalindustri; pelagisk; sjøpattedyr

Animals as instruments of Norwegian imperial authority in the interwar Arctic - Roberts, Peder; Jørgensen, Dolly (Journal for the History of Environment and Society, 2016)
During the first half of the twentieth century a number of individuals in Norway participated in the transfer of animals from both the Arctic to the Antarctic regions and vice versa. These projects may be conceptualized as a form of imperial acclimatization, following in the footsteps of earlier attempts to transplant both plants and animals from their indigenous ranges to new geographic locations for both practical and recreational purposes. Reindeer were introduced to the island of South Georgia before World War I as Norwegian whalers turned a space previously uninhabited by humans into the operational hub of a booming Antarctic whaling industry. The successful transplantation of reindeer was followed by less successful attempts to transfer muskoxen from Greenland to Svalbard and the Scandinavian mainland, penguins from the Antarctic to the coast of Norway, and dreams of transferring fur seals from south to north. We argue that these attempts constituted both practical attempts to “enrich” the fauna of discrete habitats, but also expressions of Norwegian authority over the polar regions at a time when imperial ambitions in both the Arctic and Antarctic had significant traction within Norway. The transplanted animals may thus be conceived as geopolitical instruments – mastery over fauna as being a means of expressing mastery over space.
Keywords: Antarktis; Bouvetøya; Norge; geopolitikk; hvalfangst; polarområdene

Kaptein Melsom. Et spennende liv som hvalfanger og skipsreder - Dyrhaug, Tore (Njotarøy : årsskrift, 2015)
1912 fikk Nøtterøy en ny innbygger. Hvalfangeren H. G. Melsom var vendt hjem fra et hvalfangerliv i det fjerne Østen og kjøpte hus på Ørsnes. Her startet han opp en ny fase i livet, som skipsreder. Høydepunktet i hans karriere var trolig da hvalskuta «Lancing» dro om bord den første hvalen fra en opphalingsslipp i hekken på båten. Med dette var den virkelige pelagiske hvalfangsten i gang. Historien om «Lancing» som det første hvalkokeriet som kunne dra en hel hval om bord, er vel kjent og beskrevet. Dette var starten på den pelagiske hvalfangsten som brakte hvalfangsten inn i en ny fase. Men historien om hvalfangeren og rederen fra Nøtterøy, som var en av dem som sto bak, har ikke vært særlig kjent. Med god hjelp fra barnebarnet Henrik Melsom Henriksen, har Tore Dyrhaug skrevet ned denne historien.
Keywords: Nordmenn; Norge; Sørishavet; dagbøker; hvalfangere; hvalfangst; pelagisk

Norway in the Antarctic - Rognhaug, Magnus Hovind (ed.) (Norsk Polarinstitutt, Norge Utenriksdepartementet, 2014)
Keywords: Antarktis; Antarktistraktaten; Bouvetøya; Dronning Maud Land; Norge; Peter I. Øy; ekspedisjoner; forskningsstasjoner; forvaltning; hvalfangst; klima; klimaendringer; miljø; naturressursforvaltning; naturvitenskapelig; polarforskning; polarområdene

Norge i Antarktis - Rognhaug, Magnus Hovind (red.) (Norsk Polarinstitutt, 2014)
Keywords: Antarktis; Antarktistraktaten; Bouvetøya; Dronning Maud Land; Norge; Peter I. Øy; Sørishavet; forskning; miljøvern; polarforskning; politikk

A Crisis that Never Came: The decline of the Antarctic Whaling Industry in the 1950s and 1960s - Basberg, Bjørn L (The Mariner's Mirror, 2013)
Keywords: Norge; Sørishavet; hvalfangere; hvalfangst; pelagisk; økonomi

Norges ti viktigste polarekspedisjoner - Jaklin, Asbjørn; Jølle, Harald Dag (Norsk Polarinstitutt, 2012)
Keywords: Antarktis; Carl Anton Larsen; Maudheim; NSBX 1949-52; Norge; Norsk-britisk-svenske antarktisekspedisjon; Roald Amundsen; Sydpolsekspedisjonen; polarekspedisjoner; polarforskning; polarområdene

Roald Amundsens sydpolsferd (1910-1912) = Roald Amundsen's South Pole expedition (1910-1912) - Amundsen, Roald; Diesen, Jan Anders; Lund, Harald Østgaard (Norsk filminstitutt, 2010)
Keywords: Antarktis; Fram (skip); Norge; Sydpolen; Sydpolsekspedisjonen; dokumentarfilmer; ekspedisjonsfilmer; oppdagelsesreiser; polarområdene

Whalers' wives in Vestfold, Norway during the pelagic period - Garmel, Hanne (Whaling and History III : papers presented at a symposium in Sandefjord on the 18th and 19th of June 2009, 2010)
Keywords: Norge; Sørishavet; hvalfangst; kulturhistorie; pelagisk

Who owns the history of whaling? The norwegian whaling industry and the writing of modern whaling history - Ringstad, Jan Erik (Whaling and History III : papers presented at a symposium in Sandefjord on the 18th and 19th of June 2009, 2010)
Keywords: Norge; Sørishavet; hvalfangst; kulturhistorie; pelagisk

A frozen field of dreams : science, strategy, and the Antarctic in Norway, Sweden, and the British empire, 1912-1952 : a dissertation submitted to the Department of History and the Committee on graduate studies of Stanford University in partial fulfillment of the requirements for the degree of Doctor of Philosophy - Roberts, Peder (Peder William Chellew Roberts, 2010)
Keywords: Antarktis; Norge; historie; norske ekspedisjoner; politikk

The first Antarctic whaling season of Admiralen (1905–1906): the diary of Alexander Lange - Adie, Susan; Basberg, Bjørn L; Lange, Alexander (Polar Record, 2009)
The first factory ship of the so-called modern era of Antarctic whaling was Admiralen, arriving together with two smaller catcher boats in the South Shetland Islands in January 1906, after a period of whaling in the Falkland Islands. The expedition leader was Alexander Lange, a Norwegian whaler with a long experience from whaling in northern Norway and Spitsbergen. He kept a diary for a considerable period and this covered several whaling voyages. The one dealing with the pioneer Antarctic season of 1905–1906 has been translated from Norwegian into English and is presented here with an introduction that places the expedition into its wider context.
Keywords: Nordmenn; Norge; Sørishavet; dagbøker; hvalfangere; hvalfangst; pelagisk

Norge i Antarktis : fra erobring til moderne forskning - Winther, Jan-Gunnar; Andersen, Rolf Trolle; Basberg, Bjørn L; Bomann-Larsen, Tor; Haugland, Jan Erling; Njåstad, Birgit; Orheim, Olav; Tveraa, Torkild; Monsen, Oddbjørn (Schibsted, 2008)
Keywords: Antarktis; Norge; ekspedisjoner; forskningsstasjoner; forvaltning; hvalfangst; klima; klimaendringer; miljø; naturressursforvaltning; naturvitenskapelig; polarforskning; polarområdene

Norway in the Antarctic : from conquest to modern science - Winther, Jan-Gunnar; Tveraabak, Jacob; Andersen, Rolf Trolle; Basberg, Bjørn L; Bomann-Larsen, Tor; Haugland, Jan Erling; Njåstad, Birgit; Orheim, Olav; Monsen, Oddbjørn; Goldman, Helle V (Schibsted, 2008)
Keywords: Antarktis; Norge; ekspedisjoner; forskningsstasjoner; forvaltning; hvalfangst; klima; klimaendringer; miljø; naturressursforvaltning; naturvitenskapelig; polarforskning; polarområdene

Norway and past International Polar Years—a historical account - Bones, Stian (Polar Research, 2007)
Surveying Norway’s role in past International Polar Years (IPYs), this essay by historian Stian Bones contributes to a broader understanding of Norway as a “polar nation”. He describes the strengths of Norway’s scientific traditions in the polar regions, and examines the varying motivations driving Norwegian involvement in the first three IPYs: 1882–83, 1932–33 and 1957–58 (also known as the International Geophysical Year).
Keywords: Antarktis; Det internasjonale geofysiske år (IGY); Norge; historie; polarområdene; vitenskap

Polar Research evolves, and Norway and the IPY - Goldman, Helle V (Polar Research, 2007)
Keywords: Antarktis; Det internasjonale geofysiske år (IGY); Norge; Norsk Polarinstitutt; ekspedisjoner; forskning; polarområdene; vitenskap

Norwegian-Japanese whaling relations in the early 20th century : a case of successful technology transfer - Mageli, Eldrid (Scandinavian Journal of History, 2006)
Keywords: Japan; Norge; Sørishavet; hvalindustri; pelagisk hvalfangst

Bjarne Aagaard and his Crusade against Pelagic Whaling in the late 1920s - Ringstad, Jan Erik (Whaling and History II : new perspectives, 2006)
Keywords: Norge; Sørishavet; historie; hvalfangst; pelagisk hvalfangst

Økonomi og økologi i ishavene - Kjeldstadli, Knut (Et splittet samfunn : 1905-1935, 2005)
Keywords: Norge; Sørishavet; hvalfangst; pelagisk; økologi; økonomi

Ekspedisjoner og begivenheter - Barr, Susan (Norsk polarhistorie, 2004)
Keywords: Antarktis; Nordmenn; Norge; ekspedisjoner; oppdagelsesreiser; polarfarere

Whalers, explorers and scientists: historical perspectives on the development of the antarctic whaling industry - Basberg, Bjørn L (Antarctic challenges : historical and current perspectives on Otto Nordenskjöld's Antarctic expedition 1901-1903, 2004)
Keywords: Carl Anton Larsen; Norge; Sørishavet; ekspedisjoner; forskning; historie; hvalfangere; hvalfangst; pelagisk; polarområdene

På hvalfangst under sovjetstjernen - Børresen, Dag Ingemar (Arbeiderhistorie, 2004)
Keywords: Nordmenn; Norge; Sørishavet; arbeiderbevegelse; arbeidsforhold; historie; hvalfangst; pelagisk; sjøfolk

"Havfruer" og sjøkvinner - Elstad, Åsa (Kystkvinner i Norge, 2004)
Keywords: Norge; Sørishavet; Vestfold; hvalfangst; kulturhistorie; pelagisk

Polarheltene - minner og monumenter - Eriksen, Anne (Norsk polarhistorie, 2004)
Keywords: Antarktis; Nordmenn; Norge; ekspedisjoner; polarfarere; polarområdene

Å spise kirsebær med de store - Friedman, Robert Marc (Norsk polarhistorie, 2004)
Keywords: Antarktis; Dronning Maud Land; Norge; Norsk Polarinstitutt; ekspedisjoner; forskning; oppdagelsesreiser

Klodens helse - sett fra polene - Hessen, Dag O (Norsk polarhistorie, 2004)
Keywords: Antarktis; Dronning Maud Land; Norge; ekspedisjoner; forskning; internasjonalt samarbeid

In the wake of Tønnessen and Johnsen : trends in whaling history research after 1970 - Basberg, Bjørn L (Discussion paper Norges handelshøyskole, Institutt for samfunnsøkonomi, 2003)
Keywords: Antarktis; Norge; husholdning; hvalfangere; hvalfangst; pelagisk; økonomisk historie

Storms, ice, and whales : the antarctic adventures of a Dutch artist on a Norwegian whaler - Does, Willem van der (William B. Eerdmans, 2003)
Keywords: Carl Anton Larsen; Norge; Sørishavet; ekspedisjoner; hvalfangere; hvalfangst

Bønder i Antarktis : hvalfangst og landbruk 1925-1940 - Lalla, Robert (Institutt for økonomi og ressursforvaltning, Norges landbrukshøgskole, 2003)
Keywords: Norge; Sørishavet; husholdning; hvalfangere; hvalfangst; pelagisk; økonomisk historie

Skipsdagboken fra hvalkokeriet "Pythia" : beriberi utbruddet i 1928 - Børresen, Dag Ingemar (Sandar historielag, 2002)
Keywords: Norge; Sørishavet; dagbøker; hvalfangst; hvalkokerier

Antarctica - Sale, Richard (To the ends of the Earth : the history of Polar exploration, 2002)
This text provides an insight into the early history of the Polar regions, and tells the stories of Man's first exploration of the Arctic and Antarctic, and subsequent expeditions. The history of individual Polar expeditions has been told many times, but usually only as personal accounts of individual adventures. This misses the overall context of polar exploration - why the British depended on ponies, or plant-eating animals (on the only continent where plants don't grow), why Franklin's men perished when the local Eskimos were eking out an existence around them (and reporting Franklin's demise), and why the Scandinavians were always better than anybody else. The first map of Antarctica was produced in 1556 - the Vikings visited the Arctic 1,000 years before. In 2001, the US Base at the South Pole is manned 365 days a year. The book tells the whole story of how the two last wildernesses, at either end of the world, were discovered, conquered and tamed.
Keywords: Antarktis; Belgica ekspedisjon; Carsten Egeberg Borchgrevink; Nordmenn; Norge; Roald Amundsen; Southern Cross; Sydpolsekspedisjonen; ekspedisjonen; historie; hvalfangst; oppdagelsesreiser; pelagisk; polareksspedisjoner

Antarctic Treaty: Report of the Norwegian antarctic inspection under article VII of the Antarctic Treaty ([Justis- og beredskapsdepartementet], 2001)
Article VII of the Antarctic Treaty entitles each Consultative Party to designate observers who shall have the right to carry out unannounced on-spot inspections. The purpose of these inspections is to promote the objectives of and ensure compliance with the provisions of the Antarctic Treaty and the easures adopted under it. The observers shall be accorded complete freedom of access at any time to all areas of Antarctica, including all stations within those areas, as well as vessels and aircrafts at points of embarkation and disembarkation. Article 14 of the Protocol on Environmental Protection to the Antarctic Treaty commit the Consultative Parties to undertake inspections under Article VII of the Antarctic Treaty in order to promote the protection of the Antarctic environment and dependent and associated ecosystems, and to ensure compliance with the Environmental Protocol.
Keywords: Antarktis; Norge; forskningsstasjoner

Norwegian use of the polar oceans as occupational arenas and exploration routes - Barr, Susan (Polar Record, 2001)
Keywords: Antarktis; Nordmenn; Norge; ekspedisjoner; forskning; geografi; historie; oppdagelsesreiser; polarområdene